Near-edge X-ray absorption fine structure spectroscopy in studies of self-assembled monomolecular films - Zharnikov, Michael (Journal of electron spectroscopy and related phenomena, 2023)
This article reviews the application of near-edge X-ray absorption fine structure (NEXAFS) spectroscopy to characterization of self-assembled monolayers (SAMs) which are an important part of modern nanotechnology, being particular useful in context of surface and interface engineering. NEXAFS spectroscopy provides information about the electronic structure of the SAMs, which allows to recognize specific functional groups and building blocks of the SAM-forming molecules. Due to the linear dichroism effects in X-ray absorption, this technique is also capable to give insight into orientational order and molecular orientation in the SAMs, both overall and building-block-specific. To illustrate the above points, a variety of representative examples for different classes of SAMs is provided, accompanied by the information about the general aspects of the technique and the description of suitable data evaluation procedures. Finally, it is shown that the application of NEXAFS spectroscopy to SAMs is not only limited by their characterization but is also useful to monitor chemical and physical processes involving these systems.
Online verfügbar 23. April 2023, Artikelversion 25. April 2023
Gesehen am 16.06.2023